2023
DOI: 10.3389/fntpr.2023.1169182
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and antioxidant activities of Colombian plants against paraquat and C2-ceramide exposure in SH-SY5Y cells

Abstract: Abnormal production of reactive oxygen species (ROS) has been implicated in the physiopathology of neuronal cell death. Increased ROS levels are associated with exacerbated peptide aggregation, inflammation, and mitochondrial dysfunction, which facilitate the triggering of specific cell death pathways. Antioxidant molecules are potentially useful in the amelioration of neurodegeneration. In this regard, natural products are an invaluable source of antioxidants. Therefore, we investigate the antioxidant and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“… 7 The effects shown by quercitrin producing improvement in memory by enhancing the signaling pathway Wnt/catenin and reducing reactive oxygen species (ROS) and its cholinergic inhibition activity are related to a decrease in the formation of amyloid plaque. 8 In our previous research, we have shown that quercitrin exhibits agonistic activity as evidenced through molecular docking with LXR-β and LXR-α. This flavonoid was also shown to increase the expression of mRNA in both APOE and ABCA1 target genes of LXRs as seen by in vitro experiments.…”
Section: Introductionmentioning
confidence: 95%
“… 7 The effects shown by quercitrin producing improvement in memory by enhancing the signaling pathway Wnt/catenin and reducing reactive oxygen species (ROS) and its cholinergic inhibition activity are related to a decrease in the formation of amyloid plaque. 8 In our previous research, we have shown that quercitrin exhibits agonistic activity as evidenced through molecular docking with LXR-β and LXR-α. This flavonoid was also shown to increase the expression of mRNA in both APOE and ABCA1 target genes of LXRs as seen by in vitro experiments.…”
Section: Introductionmentioning
confidence: 95%